A phase III observer-blind randomized, controlled study to evaluate the immune response and the correlation with nasopharyngeal carriage after immunization of university students with a quadrivalent meningococcal ACWY glycoconjugate or serogroup B meningococcal vaccine. Issue 3 (11th January 2017) - Read, Robert C.; Dull, Peter; Bai, Xilian; Nolan, Kate; Findlow, Jamie; Bazaz, Rohit; Kleinschmidt, Annett; McCarthy, Maggie; Wang, Huajun; Toneatto, Daniela; Borrow, Ray
Abstract: Background: University students have high rates of pharyngeal carriage of Neisseria meningitidis . Interruption of carriage acquisition is an important mechanism of vaccines for inducing herd protection. 4CMenB and MenACWY-CRM vaccines have been shown to be immunogenic against meningococcal serogroups B and ACWY respectively in younger age groups, and also to elicit a modest impact on meningococcal carriage in vaccinated students. However, vaccine responses in university students and the impact of serum bactericidal antibody (SBA) titers on meningococcal carriage are undetermined. Methods: Immunogenicity of two 4CMenB doses or one MenACWY-CRM dose was measured in university students at Months 2, 4, 6 and 12 post-first vaccination. Immunogenicity of one MenACWY-CRM dose in students with previous meningococcal serogroup C conjugate vaccination was also assessed. Immune responses were measured with an SBA assay using human complement (hSBA) against three reference strains for serogroup B and against one strain for each for serogroups C and Y. Correlations between hSBA titers and meningococcal carriage were analyzed. Results: All subjects demonstrated robust functional antibody responses to both vaccines at Month 2 and a high proportion maintained protective hSBA titers up to Month 12. At baseline, carriage of disease-associated serogroup B strains and serogroups C and Y were higher in subjects with already-protective hSBA titers. Post-vaccination, while both 4CMenB and MenACWY-CRM elicited robust immunogenicity in students, significant correlations between post-vaccination hSBA titers and carriage of disease-associated serogroups were not observed. Conclusions: 4CMenB and MenACWY-CRM were both highly immunogenic. There was no correlation between carriage and post-vaccination hSBA titers.